2023
DOI: 10.1126/sciadv.adg3736
|View full text |Cite
|
Sign up to set email alerts
|

Monocytic MDSCs exhibit superior immune suppression via adenosine and depletion of adenosine improves efficacy of immunotherapy

Abstract: Immune checkpoint inhibitor (ICI) therapy is effective against many cancers for a subset of patients; a large percentage of patients remain unresponsive to this therapy. One contributing factor to ICI resistance is accumulation of monocytic myeloid-derived suppressor cells (M-MDSCs), a subset of innate immune cells with potent immunosuppressive activity against T lymphocytes. Here, using lung, melanoma, and breast cancer mouse models, we show that CD73-expressing M-MDSCs in the tumor microenvironment (TME) exh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…MDSCs are derived from bone marrow and play a significant role in the TME. Elevated levels of MDSCs can promote tumor formation and growth as well as inhibit immune responses. , It has been reported that the CSF-1R inhibitor PLX can modulate MDSC subsets in the TME . It was observed that the ratio of CD11b + CD45 + Ly6G int Ly6C low cells was significantly decreased in ascites and tumors of the pIL-12@cR-PssPD, PLX@cR-PssP pIL-12+PLX@PssPD, and pIL-12+PLX@cR-PssPD groups, suggesting a reduction in the infiltration of granulocytic MDSCs.…”
Section: Resultsmentioning
confidence: 99%
“…MDSCs are derived from bone marrow and play a significant role in the TME. Elevated levels of MDSCs can promote tumor formation and growth as well as inhibit immune responses. , It has been reported that the CSF-1R inhibitor PLX can modulate MDSC subsets in the TME . It was observed that the ratio of CD11b + CD45 + Ly6G int Ly6C low cells was significantly decreased in ascites and tumors of the pIL-12@cR-PssPD, PLX@cR-PssP pIL-12+PLX@PssPD, and pIL-12+PLX@cR-PssPD groups, suggesting a reduction in the infiltration of granulocytic MDSCs.…”
Section: Resultsmentioning
confidence: 99%
“…BM-MDSCs were cultured as described previously [45] . In short, the tibiae and femora were removed from 12-week-old C57BL/6 J male mice to flush BM cells with PBS, after which clean BM cells were resuspended in RPMI 1640 supplemented with 40 ng/mL murine IL-6 and GM-CSF (Miltenyi Biotec, USA).…”
Section: Methodsmentioning
confidence: 99%
“…M-MDSC induced an increase in adenosine levels, and depletion of adenosine in TME using polyethylene glycolate adenosine deaminase (PEG-ADA) improved the efficacy of immune checkpoint inhibitor (ICI) therapy in mouse studies. This provides new ideas for overcoming resistance to ICI in cancer patients (Sarkar et al 2023 ).…”
Section: Targeting Mdsc-related Therapeutic Strategiesmentioning
confidence: 99%